Feminine Consciousness In the Novels’ of Shobhaa De’: Exploring Feminine Consciousness and Men-Women Relationships in Shobhaa De's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2013)
One of the primal and seminal concerns of Feminism is todeclare that a woman is a being, not an appendage but an autonomous being,capable of finding her own self. In its early stages feminism thought of Amazon– Utopias, an all-female world, but the recent trends are an indication thatit’s possible for a woman to live in the world where men also live. The deepermost concerns of the novelists in India have been the human relationships,especially men-women relationships, and the functioning of female psyche. Thecontemporary novelists are entangled in the complexities of men-womenrelationships and subtleties of feminine consciousness.